A sorrow fierce and falling - Cluess, Jessica (Cluess, Jessica. Kingdom on fire ;, 2018)
In this conclusion to the series, Henrietta and Lord Blackwood are at the estate of Sorrow-Fell where Henrietta nervously awaits her marriage to Blackwood. However, a dark secret on the estate is revealed and Henrietta realizes the estate is a trap. With Maria and Magnus at her side, Henrietta makes her stand and marches straight into the enemy's lair in a final confrontation to save the realm that will have long-lasting consequences.